PEMOCS: effects of a concept-guided, PErsonalized, MOtor-Cognitive exergame training on cognitive functions and gait in chronic Stroke—a randomized, controlled trial - Huber, S. K.; Knols, R. H.; Held, J. P. O.; Betschart, M.; Gartmann, S.; Nauer, N.; de Bruin, E. D. (Frontiers in Aging Neuroscience, 2025)
PurposeMotor-cognitive exergames may be beneficial for addressing both motor and cognitive residual impairments in chronic stroke, however, effective training schedules are yet to be determined. Therefore, this study investigates the effects of a concept-guided, personalized, motor-cognitive exergame training on cognitive functions and gait in chronic stroke survivors.MethodsIn this single-blind, randomized, controlled trial, stroke survivors (at least six-months post-stroke and able to perform step-based exergaming) were allocated either to the intervention (usual care + concept-guided, personalized, motor-cognitive exergame training) or the control group (usual care only). Global cognitive functioning was primarily targeted, while health-related quality of life (HRQoL), cognitive functions, mobility, and gait were evaluated secondarily. Analyses were performed with linear-mixed effect models.ResultsEffects on global cognitive functioning were non-significant, with no differences between responders (participants exhibiting a clinically relevant change) and non-responders (participants exhibiting no clinically relevant change). Among secondary outcomes, the mobility domain of the HRQoL questionnaire, intrinsic visual alertness, cognitive flexibility, working memory, and outdoor walking speed as well as swing width (unaffected side) showed significant interaction effects in favour of the exergame group.DiscussionAdditional exergaming helped maintaining global cognitive functioning and showed encouraging effects in mobility and cognitive outcomes. Responders and non-responders did not differ in adherence, baseline values or age. Enhancing the frequency and intensity of sessions could unlock more substantial benefits. Adopting a blended therapy approach may be key to maximizing positive effects.Clinical trial registrationclinicaltrials.gov, identifier NCT05524727.